Degradação aeróbia e anaeróbia de lixiviados de macrófitas aquáticas em função da temperatura - Silva, Roberta Mafra Freitas da (Universidade Federal de São Carlos, 2021)
Aquatic macrophytes are extremely important organisms for the maintenance of aquatic ecosystems. Among the functions performed by aquatic plants is the cycling of carbon, nitrogen and phosphorus. These elements are released into the environment mainly during the mineralization of aquatic macrophytes. The form most available and readily assimilated by microbial communities is the dissolved fraction). The objectives of the current study were to analyze the effects of temperature increase (4 ° C) on dissolved oxygen consumption and carbon decay of leachates from aquatic macrophytes Myriophyllum aquaticum, Hedychium coronarium, Salvinia auriculata and Chara sp. the effect of temperature increase and dissolved oxygen availability (comparing anaerobic and aerobic systems) on the following parameters: organic carbon, total nitrogen, total phosphorus, total polyphenols, peroxidase and polyphenol oxidase enzyme activity, E4/E6 (for determination of the quality of organic matter), secondary production, pH and conductivity. First-order kinetic models were used, using a non-linear method to determine the maximum consumption of dissolved oxygen and carbon decay over 90 days. The results demonstrate that the increase in temperature potentialized the consumption of dissolved oxygen, but the same did not occur for carbon and nitrogen mineralization. Carbon decay and secondary propagation propagation difference for dissolved oxygen availability (p < 0.05). However, temperature had no influence on this parameter (p> 0.05). For both bioassays, the leachate types dissipated difference (p < 0.05). Dissipated oxygen availability and dissipated temperature for parameters total nitrogen, total phosphorus, peroxidase and polyphenol oxidase enzyme activities, total polyphenols and E4/E6 ratio.
Aerobic and anaerobic degradation of aquatic macrophyte leachates as a function of temperature
Keywords: Aumento de temperatura; Decaimento de carbono; Consumo de oxigênio dissolvido; Matéria orgânica dissolvida; Ciclagem de nutrientes; Atividade enzimática; Temperature rise; Carbon decay; Dissolved oxygen consumption; Dissolved organic matter; Nutrient cycling; Enzymatic activity; CIENCIAS BIOLOGICAS::ECOLOGIA